2022
DOI: 10.1021/acs.orglett.2c03159
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Total Synthesis of Formosanol, Tsugacetal, and Methyl β-Conidendral

Abstract: The first enantioselective total synthesis of aryltetralin lignan acetals, (−)-formosanol, (+)-tsugacetal, (+)-methyl β-conidendral, and their enantiomers have been accomplished on the basis of the Pd-catalyzed asymmetric allylic cycloaddition as a key step. Six stereoisomers of the lignan acetals have been synthesized via a 7–8 step sequence in up to 14% overall yield. The in vitro cytotoxicity against several cancer cells has preliminarily been examined for the obtained six stereoisomers of lignan acetals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…An appropriately designed tetrahydrofuran 21i accessed from the present strategy has been utilized for the synthesis of lignin-based natural products, such as (−)-formosanol 22 and (+)-tsugacetal 23. 30 The isonucleoside motif has gained profound significance due to its high biological profile. 31 For instance, Tanzisertib 32 has been evaluated for fibrosis treatment, and BMS-181165 33 exhibits potent activity against HSV and VZN.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An appropriately designed tetrahydrofuran 21i accessed from the present strategy has been utilized for the synthesis of lignin-based natural products, such as (−)-formosanol 22 and (+)-tsugacetal 23. 30 The isonucleoside motif has gained profound significance due to its high biological profile. 31 For instance, Tanzisertib 32 has been evaluated for fibrosis treatment, and BMS-181165 33 exhibits potent activity against HSV and VZN.…”
Section: Reviewmentioning
confidence: 99%
“…An appropriately designed tetrahydrofuran 21i accessed from the present strategy has been utilized for the synthesis of lignin-based natural products, such as (−)-formosanol 22 and (+)-tsugacetal 23 . 30…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other strategies, Pd-catalyzed cycloaddition utilizing zwitterionic π–allyl palladium complexes as key intermediates offers a distinctive pathway in organic synthesis to deliver targeted molecules that are challenging to produce using conventional methods. 6 In particular, the versatile α-arylidene, derived from different scaffolds, enables the efficient and rapid synthesis of spiro-heterocycles under palladium catalysis (Scheme 1C). 7 However, the construction of spiro-pyrazolones and pyrazolone-fused spirocyclic analogues from α-arylidene still remains elusive.…”
mentioning
confidence: 99%
“…Most recently, Hou and co-workers disclosed Pd-catalyzed asymmetric allylic cycloaddition of vinyl epoxides with substituted propiolates to access 3,4,5-trisubstituted 2,3-dihydrofurans with high enantioselectivities (Scheme b) . Our group recently developed Pd-catalyzed asymmetric allylic cycloaddition of vinylethylene carbonates (VECs) with various unsaturated electrophiles to rapidly access diverse chiral oxo-heterocycles with high efficiencies . We found that the Pd-catalyzed asymmetric allylic cycloaddition of VECs with 3-cyanochromones can produce furanobenzodihydropyrans bearing three stereocenters with high stereoselectivities .…”
mentioning
confidence: 99%